Pakistan's Inter-Services Intelligence Directorate covert action and internal operations - Sirrs, Owen L. (Routledge, Taylor & Francis Group, 2017)
This book is the first comprehensive study of Pakistan's Inter-Services Intelligence Directorate (ISI). This study concludes that reforming or even eliminating ISI will be fundamental if Pakistan is to successfully transition from an army-run, national security state to a stable, democratic society that enjoys peaceful relations with its neighbours.